Caregiver burden, health utilities, and institutional service use in Alzheimer’s Disease - Miller, Edward Alan (2011)
OBJECTIVE: This study examined the moderating effect of caregiver burden on the relationship between the health status of Alzheimer’s disease (AD) patients and their use of institutional services (i.e., hospitalization, nursing home, and residential care). METHODS: Data were obtained at baseline and 3-, 6-, and 9-months following study entry on 421 community-dwelling patients with AD in the CATIE-AD trial. The outcome variable includes use of any institutional services. Logistic regression was employed to estimate the interaction of Health Utility Index (HUI)-III score (a general health status measure) at outcome and four concurrent caregiver burden measures. Marginal effects were calculated and plotted using random effects models for observations at multiple time points per individual. Average effects were calculated across all observations using models without random effects. RESULTS: Random effects results suggest that caregiver burden weakens the inverse relationship between health utilities and institutional service use, leading to greater likelihood of institutional use than would be expected at a given level of health. This is indicated by positive, significant signs on the HUI-III*caregiver burden interaction when burden is measured using the Caregiver Distress Scale, Beck Depression Inventory (BDI), and Caregiver Assessment Survey (all p<.05). It is reinforced by positive, significant average effects deriving from Caregiver Distress and BDI models without random effects (both p<.10). Results deriving from the Burden Interview Scale, though positive, were non-significant and weak by comparison. CONCLUSION: Caregiver support interventions should be offered to individuals caring for less advanced AD patients. Otherwise healthy patients may be at increased risk for institutionalization when caregivers experience high levels of burden.